Online distribution of content in the EU - Pihlajarinne, Taina; Vesala, Juha, 1976-; Honkkila, Olli (Edward Elgar Pub., 2019)
The legal issues surrounding the online distribution of content have recently gained prominence due to the European Commission's commitment to the Digital Single Market (DSM). This book is one of the first to provide highly topical analysis of the key legal challenges surrounding the online distribution of content, with particular focus on intellectual property rights, competition law and the regulation of new technologies. Central to the book is the question of whether the Commission's proposed legislative solutions will lead to a more coherent, or more fragmented, legal framework at both EU and member state level. Experts within the field assess how current legislation can be effectively applied and look ahead to examine how potential issues raised by emerging technologies, and the need to develop the online content market beyond the DSM proposal, can be anticipated and addressed. Providing a well-rounded view of the subject, this book will be of interest to scholars working within copyright, competition, and consumer law as well as those researching the development of the internal market more widely. Practising lawyers and in-house counsel who work on licensing and distribution agreements within Europe will also benefit from the analysis of new DSM legislation and associated case studies.